Pemanfaatan Limbah Kulit Jagung Sebagai Upaya Pengembangan Usaha IKM Pembuat Kertas Seni - Komariyah, Imas; Suwandi, Yudi Wahyudin; Krisnadi, Luky; Hafid, Hafid (Jurnal Pengabdian Tri Bhakti, 2020)
Design and manufacture of paper pulp machine with raw corn skin waste as one of the efforts in the development of IKM in the countryside, and other purposes to manage and utilize corn skin waste into pulp pulp so that it becomes a useful value, can even improve the economy of the community, especially in rural areas. Corn skin waste is very abundant and mostly burned, resulting in reduced soil fertility rates even feared to cause air populations. Corn skin waste processed with environmentally friendly insights, this condition that makes researchers conduct technology-based development appropriately. The manufacture of appropriate technology for the manufacture of pulp machines including: (1) design, (2) construction manufacturing, (3) trials. The results of the design and trials conducted at pulp production capacity of 200 kg/h, then the technical specifications are: (1) length = 1,250 mm, (2) width = 1,000 mm, (3) height= 1,500 mm, (4) weight= 200 kg, (5) motor power= 8 PK. From the results of operation and calculation of economic analysis is known the amount of selling price per unit is Rp 30,000,000 and the price of corn skin waste pulp is around Rp 4000 -Rp 5000/kg. The development of pulp bubr paper made from corn skin waste in collaboration with small craftsmen to make art paper, map, bag, egg place, fruit tembat, souvenirs, frames, invitation cards and others. It is expected that the machine is feasible to be applied to increase the added value of farmers, the creation of jobs and local native income (PAD).